Profile of iron deficiency anemia among junior high school students - Dewi Iriani; Alan R. Tumbelaka; Sri Sudaryati Nasar (Indonesian Pediatric Society, 2001)
Iron deficiency anemia (IDA) is a serious significant public health problem, since it’s negative impact on physicaland psycological development, behavior and work capacity. There are many risk factors influencing the development of IDA.A cross-sectional study has been conducted in 301 Junior High School students at East Jakarta in January-February 2000.A structural questionnaire, physical, cell blood count (CBC) and Serum Iron ( SI ) examinations were performed. We foundsome of the many variables were connected with IDA by using bivariat analysis. Anemia was found in 41 out of 301 students(13,6%) and only 25 children (8.3%) suffered from IDA. Among 179 female students, only 33 children (18.5%) were anemicand 20 out of 33 (12.0%) have IDA. Bivariat analysis revealed a significant association between IDA with sex, parent’seducation, food frequency questionnaire (FFQ) scores, and menstruation. It is concluded that the prevalence of IDA in thisstudy was lower than found in some previous studies in Indonesia. Gender, menstruation, low educated parents, and low FFQscores were risk factors for IDA.